Linguistic Stylistic Analysis of Instagram Poems by Rupi Kaur, Dhiman, and R.M Drake - Livia Ayudita Wiadji; Sharifah Hanidar (Lexicon, 2020)
In the era of digitalization, poems are also published on the internet. Instagram is one of many platforms to introduce self-written poems to a broader range of readers around the world. An Instagram poem has its own writing style and aesthetics since it is written in the modern era. In this research, stylistic analysis is used to analyze the style used in Instagram poems. Rupi Kaur, Dhiman, and R. M. Drake are three Instagram poets whose poems are chosen for analysis. The poems are chosen based on the number of likes. Five most liked poems of each poet written in 2018 are the main data source used in this research. The purpose of the research is to identify the linguistic features found in poems written by Rupi Kaur, Dhiman, and R.M Drake. Out of many linguistic features, only graphology, phonology, syntax, and lexical features are analyzed in this research. The result shows that Instagram poems are mostly written in lower case letters in the same font. They also form free rhymed poems by using enjambment to break the sentences into several lines. The Instagram poets also chose their words carefully to create a specific meaning in the lines while creating a balanced emotion of word connotation.